2023
DOI: 10.1155/2023/3615688
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Clustering and Survival-Related Genes of Cuproptosis in Cutaneous Melanoma

Abstract: As a highly malignant tumor, the morbidity and mortality of cutaneous melanoma (CM) are increasing year by year. A novel type of cell death connected to mitochondrial metabolism is called cuproptosis. Cuproptosis regulates tumor biological behavior. Thus, genes controlling cuproptosis could be a promising candidate bioindicator for cancer therapy. Datasets of CM patients were obtained from the public database that includes clinical information and RNA-seq data. We divided CM patients into three different subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Previous studies have indicated the involvement of 12 genes (FDX1, LIAS, LIPT1, DLD, DLAT, PDHA1, PDHB, MTF1, GLS, CDKN2A, SLC31A1 and ATP7B) in regulating copper-induced cell death, and their abnormal expression in SKCM ( Tsvetkov et al, 2022 ; Qin et al, 2023 ). Our research also identified abnormal expression of 18 Hippo pathway-related genes in SKCM ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated the involvement of 12 genes (FDX1, LIAS, LIPT1, DLD, DLAT, PDHA1, PDHB, MTF1, GLS, CDKN2A, SLC31A1 and ATP7B) in regulating copper-induced cell death, and their abnormal expression in SKCM ( Tsvetkov et al, 2022 ; Qin et al, 2023 ). Our research also identified abnormal expression of 18 Hippo pathway-related genes in SKCM ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent study found a significant difference in the expression of copper death-related genes between SKCM and normal tissues, suggesting an association between cuproptosis and the occurrence of SKCM. Additionally, they indicate that prognostic model constructed based on cuproptosis-related genes can effectively predict prognosis information for SKCM patients, highlighting the value of copper death-related genes in melanoma prognosis prediction (Qin et al, 2023). Zhou et al also develop a novel risk model based on cuproptosis-related lncRNAs, which predicted prognosis and indicated immune microenvironment landscape of patients with SKCM (Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, several studies ( Brière et al 2021 , Qin et al 2023 ) strongly advocated for the integration of modules from various methods to create more accurate and robust results. However, there is a lack of consensus clustering tools or websites that can integrate gene modules identified by different methods.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma, classified as a malignant melanocytic proliferation, can originate from melanocytes in the skin, mucosal tissues, or nervous system (3). Cutaneous melanoma is the most common form of melanoma and is characterized by aggressive behavior, propensity for metastasis, and significant impact on the patient's overall prognosis, particularly when early detection proves elusive (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%